2006
DOI: 10.1073/pnas.0607795103
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α protects skeletal muscle from atrophy by suppressing FoxO3 action and atrophy-specific gene transcription

Abstract: Maintaining muscle size and fiber composition requires contractile activity. Increased activity stimulates expression of the transcriptional coactivator PGC-1␣ (peroxisome proliferator-activated receptor ␥ coactivator 1␣), which promotes fiber-type switching from glycolytic toward more oxidative fibers. In response to disuse or denervation, but also in fasting and many systemic diseases, muscles undergo marked atrophy through a common set of transcriptional changes. FoxO family transcription factors play a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
871
7
36

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 898 publications
(995 citation statements)
references
References 52 publications
56
871
7
36
Order By: Relevance
“…PGC-1α protects against skeletal muscle atrophy ( Sandri et al 2006) and very recently it has been shown to be required for training-induced prevention of age associated decline in mitochondria (Leick et al 2010). Moreover, relevance of PGC-1α in sarcopenia and metabolic diseases during aging has been also suggested (Wenz et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGC-1α protects against skeletal muscle atrophy ( Sandri et al 2006) and very recently it has been shown to be required for training-induced prevention of age associated decline in mitochondria (Leick et al 2010). Moreover, relevance of PGC-1α in sarcopenia and metabolic diseases during aging has been also suggested (Wenz et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1α is currently identified as a new therapeutic target for treatment of age-related mitochondrial dysfunction in skeletal muscle, and more generally for sarcopenia (Sandri et al 2006). Moreover, recently, an interesting paper has underpinned the critical role of PGC-1α to link nuclear and mitcochondrial changes in aging (Kelly 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pathogenesis of neurodegenerative disorders such as Parkinson's, Alzheimer's, or Huntington's disease is generally related to an abnormal ubiquitin‐proteasome mechanism as either a primary cause or secondary consequence (Ciechanover & Brundin, 2003; Kikis et al ., 2010; Webb & Brunet, 2014). FOXOs act on both the upregulation of ubiquitin ligases and by controlling the composition of the proteasome (Bodine et al ., 2001; Sandri et al ., 2004, 2006; Stitt et al ., 2004; Vilchez et al ., 2012). However, the direct effect of FOXO‐mediated proteostasis in mammals remains to be understood.…”
Section: Foxo and Autophagymentioning
confidence: 99%
“…Foxo3 has been shown to be a transcriptional regulator of muscle‐specific E3 ubiquitin ligases, which are major effectors of protein degradation in muscle (Sandri et al ., 2004, 2006; Stitt et al ., 2004). But FOXOs can also affect the composition of the proteasome.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Importantly, in line with the mitochondrial decline, PGC‐1α expression decreases during muscle aging in different species, including humans (Ghosh et al., 2011; Kang, Chung, Diffee, & Ji, 2013; Short et al., 2005; Vina et al., 2009). Moreover, PGC‐1α improves various muscle disorders, for example, denervation‐induced fiber atrophy (Sandri et al., 2006) or Duchenne muscular dystrophy (Handschin, Kobayashi et al., 2007). Of note, conclusions about the function of PGC‐1α in the context of natural aging are difficult to extrapolate from premature aging models, for example, those with severe mitochondrial impairment.…”
Section: Introductionmentioning
confidence: 99%